An injectable bioink with rapid prototyping in the air and in-situ mild polymerization for 3D bioprinting. (22nd September 2021) - Zhou, You; Liao, Shenglong; Chu, Yanji; Yuan, Bin; Tao, Xinglei; Hu, Xiaohua; Wang, Yapei
Abstract: Bioprinting is an attractive technology for building tissues from scratch to explore entire new cell configurations, which brings numerous opportunities for biochemical research such as engineering tissues for therapeutic tissue repair or drug screening. However, bioprinting is faced with the limited number of suitable bioinks that enable bioprinting with excellent printability, high structural fidelity, physiological stability, and good biocompatibility, particularly in the case of extrusion-based bioprinting. Herein, we demonstrate a composite bioink based on gelatin, bacterial cellulose (BC), and microbial transglutaminase (mTG enzyme) with outstanding printing controllability and durable architectural integrity. BC, as a rheology modifier and mechanical enhancer component, endows the bioink with shear-thinning behavior. Moreover, the printed structure becomes robust under physiological conditions owing to the in situ chemical crosslinking catalyzed by mTG enzyme. Lattice, bowl, meniscus, and ear structures are printed to demonstrate the printing feasibility of such a composite bioink. Furthermore, the 3D-printed cell-laden constructs are proved to be a conducive biochemical environment that supports growth and proliferation of the encapsulated cells in vitro . In addition, the in vivo studies convince that the composite bioink possesses excellent biocompatibility and biodegradation. It is believed that the innovation of this new composite bioink will push forward the bioprinting technology onto a new stage.